2014
DOI: 10.1007/s12031-014-0410-8
|View full text |Cite
|
Sign up to set email alerts
|

Calcium CaV1 Channel Subtype mRNA Expression in Parkinson’s Disease Examined by In Situ Hybridization

Abstract: The factors which make some neurons vulnerable to neurodegeneration in Parkinson's disease while others remain resistant are not fully understood. Studies in animal models of Parkinson's disease suggest that preferential use of CaV1.3 subtypes by neurons may contribute to the neurodegenerative process by increasing mitochondrial oxidant stress. This study quantified the level of mRNA for the CaV1 subtypes found in the brain by in situ hybridization using CaV1 subtype-specific [(35)S]-radiolabelled oligonucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…An action on the early phase can also be envisioned if expression of CaV1.3 channels partly is regulated by negative feedback from average cytosolic calcium levels. The increased levels of CaV1.3 antigen and mRNA in cortical tissue with no Lewy body pathology from early PD patients [4,5] could represent a response to soluble AS oligomers activating SERCA and reducing average Ca 2+ in neurons not exhibiting spontaneous pace making changes in Ca 2+ as in dopaminergic neurons of substantia nigra pars compacta. The ongoing clinical study of early PD patients treated with L-type Ca channel antagonist isradipine may inform about these issues in the near future (ClinicalTrials.gov Identifier: NCT02168842).…”
Section: Discussionmentioning
confidence: 99%
“…An action on the early phase can also be envisioned if expression of CaV1.3 channels partly is regulated by negative feedback from average cytosolic calcium levels. The increased levels of CaV1.3 antigen and mRNA in cortical tissue with no Lewy body pathology from early PD patients [4,5] could represent a response to soluble AS oligomers activating SERCA and reducing average Ca 2+ in neurons not exhibiting spontaneous pace making changes in Ca 2+ as in dopaminergic neurons of substantia nigra pars compacta. The ongoing clinical study of early PD patients treated with L-type Ca channel antagonist isradipine may inform about these issues in the near future (ClinicalTrials.gov Identifier: NCT02168842).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, prodromal alterations in motor cortex plasticity are supported by pathological investigations on Ca 2+ channels, which are critical in the regulation of cortical excitability and plasticity (Wankerl et al, 2010;Verhoog et al, 2013;Weise et al, 2017). Specifically, recent postmortem studies show increased expression of L-type voltagegated Ca 2+ channels in the primary motor cortex at least as early as Braak's stages III-IV (Hurley et al, 2013(Hurley et al, , 2015b, and molecular alterations in motor cortical areas have also been reported in incidental Lewy body disease at Braak's stages I-II (Hurley et al, 2015a;Santpere et al, 2018). Motor cortical areas thus seem to be altered well before the appearance of cortical Lewy pathology (Braak's stages V-VI) and before the onset of motor features in PD.…”
Section: Evidence For Primary Cortical Involvement In Parkinson's Dismentioning
confidence: 99%
“…Sustained Ca 2+ entry through Cav1 channels in forebrain neurons has long been associated with aging-related cognitive decline and AD (Disterhoft et al, 1994; Thibault et al, 2007). Moreover, in cPD patients, Cav1 Ca 2+ channels are up-regulated in limbic and motor cortices (Hurley et al, 2013; 2014). …”
Section: The Rationale For a Cav1 Ca2+ Channel Inhibitormentioning
confidence: 99%